Europe and the East
1 online resource.
Keywords: "This volume investigates competing ideas, images, and stereotypes of a European 'East', exploring its role in defining European and national conceptions of self and other since the eighteenth century. Europe and the East will be essential reading for anyone interested in images and ideas of Europe, European identity, and conceptions of the 'East' in intellectual and cultural history"--